The effect of summer drought on the yield of Arundo donax is reduced by the retention of photosynthetic capacity and leaf growth later in the growing season - Haworth, Matthew (Ann Bot, 2019)
BACKGROUND AND AIMS: The development of Arundo donax as a biomass crop for use on drought-prone marginal lands in areas with warm to hot climates is constrained by the lack of variation within this species. We investigated the effect of morphological and physiological variation on growth and tolerance to drought under field conditions in three ecotypes of A. donax collected from habitats representing a climate gradient: a pre-desert in Morocco, a semi-arid Mediterranean climate in southern Italy and a warm sub-humid region of central Italy. METHODS: The three A. donax ecotypes were grown under irrigated and rain-fed conditions in a common garden field trial in a region with a semi-arid Mediterranean climate. Physiological and morphological characteristics, and carbohydrate metabolism of the ecotypes were recorded to establish which traits were associated with yield and/or drought tolerance. KEY RESULTS: Variation was observed between the A. donax ecotypes. The ecotype from the most arid habitat produced the highest biomass yield. Stem height and the retention of photosynthetic capacity later in the year were key traits associated with differences in biomass yield. The downregulation of photosynthetic capacity was not associated with changes in foliar concentrations of sugars or starch. Rain-fed plants maintained photosynthesis and growth later in the year compared with irrigated plants that began to senescence earlier, thus minimizing the difference in yield. Effective stomatal control prevented excessive water loss, and the emission of isoprene stabilized photosynthetic membranes under drought and heat stress in A. donax plants grown under rain-fed conditions without supplementary irrigation. CONCLUSIONS: Arundo donax is well adapted to cultivation in drought-prone areas with warm to hot climates. None of the A. donax ecotypes exhibited all of the desired traits consistent with an ‘ideotype’. Breeding or genetic (identification of quantitative trait loci) improvement of A. donax should select ecotypes on the basis of stem morphology and the retention of photosynthetic capacity.